Code Switching Used by Agnes Monica on Deddy Corbuzier’s Podcast - Rapini, Ni Komang (Universitas Pendidikan Ganesha, 2022)
Code-switching is important and widely used, someone feels they have to change the language used in order to communicate well and smoothly between each other. The research was conducted with the aim to analyses the types of Code-Switching used in Video Podcasts on the Deddy Corbuzier Channel with Agnes Monica. The data analysis technique used is descriptive qualitative with in-depth analysis techniques about the types of Code-Switching. Some methods in collecting data such as, searching the video, watch the video carefully and analyze the code-swtching. After analyzing, the researcher found the 40 data and the researcher got Inter-sentential switching 12(30%), Intra-sentential switching 8(20%), Tag-switching 3(8%) and Intra-word Switching 17 (42%) and the Intra-word Switching is dominant type of code switching used by Agnez Monica on podcast Deddy Corbuzier in YouTube. The data with persentage 36% from 9 data.